2006
DOI: 10.1111/j.1348-0421.2006.tb03839.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Epizootiology ofChlamydophila psittaciPrevalent among the Captive and Feral Avian Species Based on VD2 Region ofompAGene

Abstract: To study genetic diversity and occurrence of Chlamydophila psittaci, a total of 1,147 samples from 11 avian orders including 53 genera and 113 species of feral and captive birds were examined using ompA gene based nested PCR. Three types of chlamydiae: C. psittaci (94.12%), C. abortus (4.41%) and unknown Chlamydophila sp. (1.47%) were identified among 68 (5.93%) positive samples (Psittaciformes‐59, Ciconiiformes‐8 and Passeriformes‐1). Based on nucleotide sequence variations in the VD2 region of ompA gene, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 42 publications
3
35
0
1
Order By: Relevance
“…While representatives of avian C . abortus were rarely encountered in previous studies [1011, 16, 41], the present study shows for the first time that avian genotypes of C . abortus strains are actively circulating in wild bird populations.…”
Section: Discussionsupporting
confidence: 59%
“…While representatives of avian C . abortus were rarely encountered in previous studies [1011, 16, 41], the present study shows for the first time that avian genotypes of C . abortus strains are actively circulating in wild bird populations.…”
Section: Discussionsupporting
confidence: 59%
“…The cDNA was amplified by PCR using each primer. Custom primer sets specific for C. felis cf0218 (5Ј-CGGGA TCCATGACAACAAACTCATTG-3Ј and 5Ј-GCGTCGACTTAATTAGCGTC ATCATT-3Ј) were used to detect cf0218-specific message, whereas previously described primers were used to examine levels of Chlamydophila ompA (CMGP-2F, 5Ј-GCCTTAAACATCTGGGATCG-3Ј, and CMGP-2R, 5Ј-GCACAACCA CATTCCCATAAAG-3Ј) (8). C. felis genomic DNA was used as a positive control, and total RNA samples without reverse transcription were used as controls for DNA contamination.…”
Section: Felis Cf0218 As An Infection-specific Antigen 1607mentioning
confidence: 99%
“…Parrot, parakeet and feral pigeon are the best known as representative natural hosts. Recently, we reported that 6.0% of pet birds (11 avian orders) in Japan were positive for C. psittaci [3]. Wild birds, especially pigeon, can serve as a source of human psittacosis [18,27].…”
mentioning
confidence: 99%
“…The sensitivity of the real-time PCR was compared with that of the nested PCR routinely used in our laboratory for clinical diagnosis [3]. Template DNA samples extracted from feces and PBS containing known titers of EB as described above were analyzed by nested PCR.…”
mentioning
confidence: 99%
See 1 more Smart Citation